Model pembelajaran ICT Literacy M-Learning untuk meningkatkan hasil belajar mata pelajaran Pendidikan Agama Islam di MTs. Brawijaya Mojokerto - Arief, Mochamad Budi (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2016)
Development learning model M-Learning to improve learning outcomes subjects of Islamic education is meant to provide teaching materials appropriate to the characteristics of the students. The focus in this study a learning product M-Learning to improve learning outcomes subjects of Islamic education in MTs. Brawijaya Mojokerto. Learning product M-Learning to improve learning outcomes subjects of Islamic education in MTs. Brawijaya Mojokerto has been refined based on the analysis of trial data. Based on the measures that have been implemented can be concluded as follows. 1). Products developed interesting for classical learning in the classroom and independently. 2) The products of this product can ease the burden of teachers in teaching. 3) The results of expert validation and testing, learning model M-Learning is feasible used for subjects Religious Education Islam.4) Judging the results of analysis of the quality of the learning model M-Learning can be concluded that the RPP / Scenario Learning is already fit for use for test try because the score of each component which is an indicator for learning model M-learning is no less than 3.0. 5) The results of the questionnaire data processing of learning by using learning model M-Learning is known that the average student's choice is 3:53, it is considered Enough with standard deviations 0:35 By the conclusion of this study, it can be suggested things as follows.1) Remaining time in learning if there should be used to repeat learning for students. 2) learning model developed M-Learning can also be used as a task that can be given at the time the teacher was unable to attend. 3) Products M-Learning learning model can be developed by educators, especially teachers of Islamic education so that learning becomes more fun and motivating students. The development of further research can be done by utilizing the learning model M-Learning is more interesting.